Phylodynamic of Tomato Brown Rugose Fruit Virus and Tomato Chlorosis Virus, Two Emergent Viruses in Mixed Infections in Argentina - Ibanez, Julia Magali; Zambrana Montaño, Romina Micaela; Gonzalez Carreras, Pamela Stefanía; Obregon, Veronica Gabriela; Irazoqui, Jose Matias; Vera, Pablo Alfredo; Lattar, Tatiana Elisabet; Blanco Fernandez, María D.; Puebla, Andrea Fabiana; Amadio, Ariel; Torres, Carolina; Lopez Lambertini, Paola Maria (MDPI, 2025)
Tobamovirus fructirugosum (ToBRFV) and Crinivirus tomatichlorosis (ToCV) are emerging viral threats to tomato production worldwide, with expanding global distribution. Both viruses exhibit distinct biological characteristics and transmission mechanisms that influence their spread. This study aimed to reconstruct the complete genomes of ToBRFV and ToCV from infected tomato plants and wastewater samples in Argentina to explore their global evolutionary dynamics. Additionally, it compared the genetic diversity of ToBRFV in plant tissue and sewage samples. Using metagenomic analysis, the complete genome sequences of two ToBRFV isolates and two ToCV isolates from co-infected tomatoes, along with four ToBRFV isolates from sewage, were obtained. The analysis showed that ToBRFV exhibited higher genetic diversity in environmental samples than in plant samples. Phylodynamic analysis indicated that both viruses had a recent, single introduction in Argentina but predicted different times for ancestral diversification. The evolutionary analysis estimated that ToBRFV began its global diversification in June 2013 in Israel, with rapid diversification and exponential growth until 2020, after which the effective population size declined. Moreover, ToCV’s global expansion was characterized by exponential growth from 1979 to 2010, with Turkey identified as the most probable location with the current data available. This study highlights how sequencing and monitoring plant viruses can enhance our understanding of their global spread and impact on agriculture.